Analgesic effectiveness of acetaminophen for primary cleft palate repair in young children: a randomized placebo controlled trial. Issue 6 (2nd April 2014) - Nour, Chelan; Ratsiu, Joanna; Singh, Neeta; Mason, Linda; Ray, Andrea; Martin, Mark; Hassanian, Mohammad; Uhler, Jacob; Applegate, Richard L.; Anderson, Brian
Summary Background Clefting of the lip, palate, or both is a common congenital abnormality. Inadequate treatment for pain in children may result from concerns over opioid‐related adverse effects. Providing adequate pain control with minimal adverse effects remains challenging in children. Objectives To assess opioid‐sparing effects of oral or intravenous acetaminophen following primary cleft palate repair in children. Methods Prospective randomized controlled trial in 45 healthy children, ages 5 months to 5 years, using standardized general anesthesia and lidocaine infiltration of the operative field. Patients were allocated to groups: intravenous acetaminophen/oral placebo (intravenous), oral acetaminophen/intravenous placebo (oral), or intravenous/oral placebo (control). Groups were compared for differences in opioid administration during the 24‐h study period (morphine equivalents µg·kg−1; 95% confidence interval). Results Intravenous acetaminophen decreased opioid requirement after surgery (P = 0.003). Patients in the intravenous group received less opioid (272.9; 202.9–342.8 µg·kg−1) than control patients (454.2; 384.3–524.2 µg·kg−1; P < 0.002). Opioid requirement in oral patients (376.5; 304.1–448.9 µg·kg−1) was intermediate and not significantly different from either intravenous (P = 0.11) or control (P = 0.27). During the ward phase of care, intravenous had better analgesia than control (P = 0.002), and both intravenous and oral group patients received less opioid than control (P = 0.01). Conclusion Intravenous acetaminophen given to young children undergoing primary cleft palate repair was associated with opioid‐sparing effects compared to placebo. The fewer morphine doses during ward stay in both intravenous and oral may be important clinically in some settings.